Network pharmacology-based and experimental identification of the effects of Renshen Yangrong decoction on myocardial infarction - Zhao, Jiahao; Xu, Xing; Yang, Xiaolong (Frontiers in Pharmacology, 2022)
Objective: Myocardial infarction (MI) is one of the leading causes of death worldwide. Currently, the drugs used to treat MI have various side effects. Emerging evidence supports the protective effects of Renshen Yangrong Decoction (RSYRD) in cardiovascular diseases (CVDs) treatments, with few side effect reports. However, the role of RSYRD in MI remains unclear. In this study, network pharmacological analysis was combined with experiments in vivo and in vitro to validate the effects of RSYRD in the treatment during the early stage of MI. Methods: Firstly, network pharmacology analysis was performed to search for the potential targets and signaling pathways of RSYRD in the early stage of MI. Then, the protein-protein interaction (PPI) network was constructed to identify the core genes of RSYRD that may play a key role in MI. At last, the treatment effectiveness of RSYRD on MI was verified via experiments in vitro and in vivo. Results: RSYRD contained fifty-six bioactive components. Eighty-eight intersections between RSYRD and MI targets and thirteen core genes were screened. KEGG and GO functional enrichment analyses predicted that RSYRD might play a therapeutic role in MI through oxidative stress, apoptosis, and immune-inflammatory signaling pathways. In vivo and in vitro experiment results revealed that significant apoptosis occurred in myocardial tissue in the early stage of MI. Moreover, the levels of reactive oxide species (ROS), TNF-α, and IL-6 increased markedly. After RSYRD administration, they significantly decreased. At the mechanistic level, RSYRD could reduce ROS production to alleviate cell apoptosis. Conclusion: RSYRD could reduce neonatal mouse cardiomyocytes (NMCMs) apoptosis by lowering ROS production induced by hypoxia and improve the cardiac function of mice 3 days post-MI. RSYRD could also reduce the levels of TNF-α and IL-6 in the serum of mice.